Perancangan Kartu CETAR (Cek Tekanan Darah Rutin) - Ahmad Zerri Fardian; Andri Candra; Anita Anita; Desri Nuryani; Yati Sholehatun Nisa; Tita Septi Handayani (CV. Era Digital Nusantara, 2025)
Blood pressure is a force that works by flowing blood through the walls of the body's arteries, the main blood vessels in the body. Hypertension occurs when blood pressure is too high (WHO, 2019). Hypertension can occur due to the role of various risk factors, which include risk factors that cannot be controlled (major) or those that can be controlled (minor). Risk factors that cannot be controlled (major) include heredity, gender, race and age (Susanto, 2015). According to Umpierre et al (2019), age is a risk factor for hypertension. Hypertension is a clinical condition that is very common in the elderly, can cause a large risk of cardiovascular disease and loss of quality of life for the elderly. Hypertension reminder cards can increase knowledge of treatment and compliance with medication consumption (Setianiet al., 2021).